A Comparison of Creatine and Thiamine Supplementation on Heart Rate Recovery and Blood Lactate Levels - Muhammad Danial; Hari Setijono; Nining Widyah Kusnanik (Britain International of Exact Sciences (BIoEx) Journal, 2020)
The purpose of the study was to compare the effect of creatine and thiamine supplementation on heart rate recovery (HRR) and blood lactate levels. Twelve male students comprised the two experimental (creatine and thiamine) groups of the study. The creatine group was supplemented with 0,3 g per weight, with 30 ml of water per dose of creatine four times a day, at regular intervals during the day, for 6 consecutive days. The thiamine group received 10 mg per weight just one time 30 minutes after a meal with 150 ml of water at the last supplementation days. After the supplementation period, subjects completed the incremental treadmill after a dynamic warm-up that consisted of walking at 6 km/h for 3 minutes. An initial treadmill speed started with 8,64 km/h for two minutes at 0% gradient followed by an increase of 1,44 km/h every 30 s until subjects reached their volitional exhaustion. After exercise cessation subjects continued with an active recovery of 10.08 km/h for approximately 5 minutes. Heart rate (HR) was regularly assessed from the first 5 min of passive recovery. Blood lactate levels were measured in the 9th min of passive recovery. There were no statistically significant differences in heart rate recovery and blood lactate levels after supplementation, respectively (P > 0.05). Based on these results, it appears that creatine supplementation did not provide a different effect with thiamine on the recovery of heart rate and blood lactate levels.